(untitled) (Experimental biology, 2016)
For creating domestic long-grain rice varieties adapted to soil and climatic conditions hybridization was carried out using local and foreign long grain rice varieties at IPBB. 2 local and 7 foreign rice genotypes were used as a research material. Pneumo-castration and TVEL method of pollination was used. Castration was performed using by pneumo-castration apparatus created at IPBB in the greenhouse conditions. In the amount of 5876 seeds from 17 different combinations were obtained F1 hybrids that are the source material for long grain rice breeding and their grain shape was determined by method of Kostyleva P.I. As result of the study all received hybrids of F1 generation have had long-grain (ratio l/b was 4.1-4.3).